2010
DOI: 10.1245/s10434-010-1045-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Outcomes after Percutaneous Biliary Drainage for Malignant Biliary Obstruction

Abstract: Purpose Percutaneous biliary drainage (PBD) is used to relieve malignant bile duct obstruction (MBO) when endoscopic drainage is not feasible. Little is known about the effects of PBD on the quality of life (QoL) in patients with MBO. The aim of this study was to evaluate changes in QoL and pruritus after PBD and to explore the variables that impact these changes. Patients and Methods Eligible patients reported their QoL and pruritus before and after PBD using the Functional Assessment of Cancer Therapy – He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 28 publications
7
51
2
Order By: Relevance
“…Though some reports suggested that patients with advanced malignant biliary obstruction, who were beyond chemotherapy, should not be offered PTBD; [11] other studies have shown improvement in pruritus and other high-bilirubin symptoms post procedure due to drop in bilirubin levels. [14,26] In one study, the patients' quality of life was observed to improve after PTBD despite that serum bilirubin level did not drop down to normal; where mean serum bilirubin level before PTBD was 19.85 mg/dL and after the procedure at 1 month it became 6.02 mg/dL. [27] Unfortunately, due to the retrospective nature of our study, we could not evaluate for patients' quality of life, pre-and post-procedure.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Though some reports suggested that patients with advanced malignant biliary obstruction, who were beyond chemotherapy, should not be offered PTBD; [11] other studies have shown improvement in pruritus and other high-bilirubin symptoms post procedure due to drop in bilirubin levels. [14,26] In one study, the patients' quality of life was observed to improve after PTBD despite that serum bilirubin level did not drop down to normal; where mean serum bilirubin level before PTBD was 19.85 mg/dL and after the procedure at 1 month it became 6.02 mg/dL. [27] Unfortunately, due to the retrospective nature of our study, we could not evaluate for patients' quality of life, pre-and post-procedure.…”
Section: Discussionmentioning
confidence: 90%
“…PTBD was shown in a prospective study done by Robson et al to significantly reduce the severity of pruritus. [14] However, there is mixed results with regards to the effect of PTBD on the quality of life. PTBD is an intervention that is not free of complications.…”
Section: Introductionmentioning
confidence: 99%
“…While PBD catheter insertion may improve symptoms related to hyperbilirubinemia and mitigate cholangitis in patients with extensive hepatic tumor burden, subjective measures of symptom improvement and other quality of life measures such as PBD-related discomfort were not reliably available in the medical records. In a prospective study investigating quality of life measures in patients with unresectable malignant bile duct obstruction, measures of pruritus were improved following the procedure, but quality of life was not (14). It is clear that the goals of intervention should be discussed with the patient and caregivers (15), since PBD insertion can be a cause of major and minor complications (16).…”
Section: Discussionmentioning
confidence: 99%
“…A third study examined 109 patients (94% with advanced disease) and found a statistically significant improvement in pruritus at one month (2.26–0.75; P < 0.01), using a visual analogue scale, but a significant decrease in QOL (101.3–94.7; P < 0.01), using the Functional Assessment of Cancer Therapy-Hepatobiliary instrument. 10 …”
Section: Resultsmentioning
confidence: 99%